Polymer precursor and preparation method thereof, polymer coating and preparation method thereof, negative current collector and lithium ion battery

By applying a polymer coating prepared by a polymer precursor on the negative electrode current collector surface of the lithium-ion battery, the formation of LiBr and LiF phases in the SEI layer is induced, which solves the problem of poor interface stability of the lithium-ion battery and significantly improves the electrochemical performance of the battery.

CN119504828AActive Publication Date: 2025-02-25LIONGO (CHANGZHOU) NEW ENERGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411620693.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-25
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

During the charging and discharging cycle of existing lithium-ion batteries, stable electrode-electrolyte interfaces are difficult to achieve, which affects battery performance. Especially during the initial charging and discharging process, the SEI film regulation effect is poor, resulting in unstable battery performance.

Method used

A polymer precursor is used to prepare a polymer coating. The coating has a central structure of an imidazole-like ionic liquid, including bromine anions and anchored cationic groups, and is introduced to the negative current collector surface of the lithium-ion battery, induced the formation of LiBr and LiF phases in the SEI layer, and improved the interfacial lithium ion transport stability.

Benefits of technology

By manually regulating the composition of the SEI film, the electrochemical performance of lithium-ion batteries is improved, the mechanical strength and electrochemical stability of the SEI film are enhanced, and the high-temperature cycling and rate performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504828A_ABST
    Figure CN119504828A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and particularly relates to a polymer precursor and a preparation method thereof, a polymer coating and a preparation method thereof, a negative current collector and a lithium ion battery. The chemical structure of the polymer precursor provided by the invention is shown as a formula A. In the formula A, X is Br, and R1 and R2 are selected from one or more of methyl, cyano, ethynyl, hydrogen atoms, fluorine atoms and trifluoromethyl. The polymer coating formed by the polymer precursor provided by the invention has a center structure similar to imidazole ionic liquid, is introduced into a lithium ion battery as a surface coating of a negative electrode current collector, and can be artificially induced to form a high-performance solid electrolyte interface film at a negative electrode, so that the stability of interface lithium ion transmission is improved, and the service life of the lithium ion battery is prolonged. Therefore, the electrochemical performance of the lithium ion battery is improved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and in particular relates to a polymer precursor and a preparation method thereof, a polymer coating and a preparation method thereof, a negative electrode current collector and a lithium ion battery. Background Art

[0002] Since the industrialization of lithium batteries, as an efficient energy storage system, from various electronic products to electric vehicles, and then to the expanded application of grid-scale energy storage, lithium batteries have been involved in the important process of energy ecological evolution and are increasingly closely related to people's lives. In the past few decades, lithium-ion batteries have always occupied a very important dominant position in the process of scientific and technological development, and higher-performance lithium-ion batteries are its main development direction. In the charge and discharge cycle of lithium-ion batteries, a stable electrode-electrolyte interface is crucial. Related research shows that during the initial charge and discharge process, the solid electrolyte (SEI) film formed on the electrode surface plays an important role in the performance of the battery. Therefore, artificial positive regulation of the SEI film can greatly and effectively improve the electrochemical performance of lithium-ion batteries.

[0003] At present, the reasonable regulation of SEI film is mostly achieved by adding electrolyte additives with lower LUMO energy levels to the electrolyte, so that it preferentially undergoes reduction reaction on the negative electrode surface to form a film to protect the negative electrode interface, such as vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, etc. However, these functional additives often require certain restrictions on storage conditions, otherwise it will cause the electrolyte to fail. At the same time, in order to achieve better performance, a large amount of additives are often required, which will affect the ionic conductivity of the electrolyte to a certain extent, making it unable to meet the needs of fast charging. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a polymer precursor and a preparation method thereof, a polymer coating and a preparation method thereof, a negative electrode current collector and a lithium ion battery. The polymer coating formed by the polymer precursor provided by the present invention has a central structure similar to an imidazolium ionic liquid, which is introduced into a lithium ion battery as a surface coating of the negative electrode current collector. The bromine anions in the structure are easy to combine with lithium ions to induce the formation of LiBr phase in the SEI layer, and LiBr has a low lithium ion diffusion barrier in the SEI layer, thereby improving the stability of interfacial lithium ion transmission. At the same time, the anchored cationic group can make the anions in the electrolyte, i.e., PF 6- , enriched at the negative electrode interface, and then more anions participate in the formation of the negative electrode SEI film. The formed SEI film contains more LiF phases with high mechanical strength and high electrochemical stability. Therefore, the lithium-ion battery containing this SEI film induced by artificial control means has achieved excellent electrochemical performance.

[0005] The present invention provides a polymer precursor, the chemical structure of which is shown in Formula A:

[0006]

[0007] Wherein, X is Br, and R1 and R2 are selected from one or more of a methyl group, a cyano group, an ethynyl group, a hydrogen atom, a fluorine atom and a trifluoromethyl group.

[0008] Preferably, the polymer precursor is at least one of the compounds of formula (I) to formula (VI):

[0009]

[0010] The present invention provides a method for preparing a polymer precursor, comprising the following steps:

[0011] a) subjecting an o-diamino compound of formula a to an addition reaction with butenedial to obtain a diimidazole intermediate of formula b;

[0012] b) grafting the diimidazole intermediate of formula b with chloromethylethyldimethylsilane to obtain an intermediate of formula c;

[0013] c) reacting the intermediate of formula c with a halogenated olefin of formula d to obtain a polymer precursor of formula a;

[0014]

[0015] Wherein, X is Br, and R1 and R2 are independently selected from one or more of a methyl group, a cyano group, an ethynyl group, a hydrogen atom, a fluorine atom and a trifluoromethyl group.

[0016] The present invention provides a polymer coating, wherein raw materials for preparing the polymer coating include a polymer precursor and a free radical initiator, and the polymer precursor is the polymer precursor described in the above technical solution or a polymer precursor prepared by the preparation method described in the above technical solution.

[0017] Preferably, the free radical initiator is one or more of a peroxide initiator, an azo compound initiator and a redox initiator; and the mass ratio of the polymer precursor to the free radical initiator is 7.5:(0.02-0.1).

[0018] Preferably, the preparation raw materials also include a binder and a conductive agent; the binder is one or more of an acrylic binder, polyvinyl alcohol and sodium carboxymethyl cellulose; the conductive agent is one or more of acetylene black, natural graphite and artificial graphite; the mass ratio of the polymer precursor, the binder and the conductive agent is 7.5:(3-7):(6-10).

[0019] The present invention provides a method for preparing the polymer coating described in the above technical solution, comprising the following steps:

[0020] The raw materials for preparing the polymer coating are mixed with water, coated, and baked to obtain the polymer coating.

[0021] The present invention provides a negative electrode current collector, which comprises a negative electrode current collector substrate and a coating coated on the surface of the negative electrode current collector substrate, wherein the coating is the polymer coating described in the above technical solution or the polymer coating prepared by the preparation method described in the above technical solution.

[0022] Preferably, the negative electrode current collector substrate is made of copper.

[0023] The present invention provides a lithium ion battery, wherein the negative electrode current collector of the lithium ion battery is the negative electrode current collector described in the above technical solution.

[0024] Compared with the prior art, the present invention provides a polymer precursor and a preparation method thereof, a polymer coating and a preparation method thereof, a negative electrode current collector and a lithium ion battery. The chemical structure of the polymer precursor provided by the present invention is shown in Formula A, wherein X is Br, and R1 and R2 are selected from one or more of methyl, cyano, ethynyl, vinyl, fluorine atom and trifluoromethyl. The polymer coating formed by the polymer precursor provided by the present invention has a central structure similar to an imidazolium ionic liquid, which is introduced into a lithium ion battery as a surface coating of the negative electrode current collector. The bromine anions in the structure are easily combined with lithium ions to induce the formation of a LiBr phase in the SEI layer, and LiBr has a low lithium ion diffusion energy barrier in the SEI layer, thereby improving the interfacial lithium ion transport stability. In addition, since the polymer coating structure on the surface of the negative electrode current collector is anchored with abundant cationic groups, more anions (PF) in the electrolyte can be attracted by charge attraction. 6- ) is enriched on the negative electrode surface and participates in the negative electrode film formation, which helps to further improve the mechanical strength of the SEI film and the electrochemical performance of the lithium-ion battery. The technical solution provided by the present invention does not focus on regulating the SEI film by adding additives to the electrolyte, but provides a new solution for artificial positive regulation of the SEI film. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The present invention provides a polymer precursor, the chemical structure of which is shown in Formula A:

[0027]

[0028] Wherein, X is Br, and R1 and R2 are independently selected from one or more of a methyl group, a cyano group, an ethynyl group, a hydrogen atom, a fluorine atom and a trifluoromethyl group.

[0029] In the present invention, the polymer precursor may be at least one of the compounds of formula (I) to formula (VI):

[0030]

[0031] The present invention also provides a method for preparing the polymer precursor described in the above technical solution, comprising the following steps:

[0032] a) subjecting an o-diamino compound of formula a to an addition reaction with butenedial to obtain a diimidazole intermediate of formula b;

[0033] b) grafting the diimidazole intermediate of formula b with chloromethylethyldimethylsilane to obtain an intermediate of formula c;

[0034] c) reacting the intermediate of formula c with a halogenated olefin of formula d to obtain a polymer precursor of formula a;

[0035]

[0036] Wherein, X is Br, and R1 and R2 are independently selected from one or more of methyl, cyano, ethynyl, vinyl, fluorine atom and trifluoromethyl.

[0037] In the preparation method provided by the present invention, in step a), the molar ratio of the o-diamino compound of formula a to butenedial is preferably (1.5-2.5):1, specifically 2:1.

[0038] In the preparation method provided by the present invention, in step a), the addition reaction is preferably carried out in a protective gas atmosphere, and the protective gas is preferably nitrogen; the addition reaction is preferably carried out in the presence of a catalyst, and the catalyst is preferably p-benzoquinone, and the molar ratio of p-benzoquinone to the o-diamino compound of formula a is preferably 1:(0.5-2), specifically 1:1; the addition reaction is preferably carried out in an organic solvent, and the organic solvent is preferably ethanol.

[0039] In the preparation method provided by the present invention, in step a), the specific process of the addition reaction preferably includes: first reacting at a first temperature for a period of time, and then reacting at a second temperature for a period of time; wherein the first temperature is preferably 70-90°C, specifically 80°C; the reaction time at the first temperature is preferably 2-6h, specifically 4h; the second temperature is preferably 15-35°C, specifically 25°C (room temperature); the reaction time at the second temperature is preferably 2-6h, specifically 4h.

[0040] In the preparation method provided by the present invention, in step a), after the addition reaction is completed, the product is post-treated, and the post-treatment process preferably includes: performing reduced pressure distillation, washing, extraction, drying and rotary evaporation in sequence.

[0041] In the preparation method provided by the present invention, in step b), the molar ratio of the diimidazole intermediate of formula b to chloromethylethyldimethylsilane is preferably 1:(1.5-2.5), specifically 1:2.

[0042] In the preparation method provided by the present invention, in step b), the grafting reaction is preferably carried out in a protective gas atmosphere, and the protective gas is preferably nitrogen; the grafting reaction is preferably carried out in the presence of an alkali metal hydroxide, and the alkali metal hydroxide is preferably potassium hydroxide, and the molar ratio of the alkali metal hydroxide to the diimidazole intermediate of formula b is preferably (7-9):3, specifically 8.2:3; the grafting reaction is preferably carried out in an organic solvent, and the organic solvent is preferably dimethyl sulfoxide (DMSO).

[0043] In the preparation method provided by the present invention, in step b), the temperature of the grafting reaction is preferably 15-35°C, specifically 25°C (room temperature); the time of the grafting reaction is preferably 1-5h, specifically 3h.

[0044] In the preparation method provided by the present invention, in step b), after the grafting reaction is completed, the product is post-treated, and the post-treatment process preferably includes: low-temperature extraction, reduced-pressure distillation and chromatographic purification in sequence.

[0045] In the preparation method provided by the present invention, in step c), the molar ratio of the intermediate of formula c to the halogenated olefin of formula d is preferably 50:(70-130), specifically 50:105.

[0046] In the preparation method provided by the present invention, in step c), the reaction is preferably carried out in a protective gas atmosphere, and the protective gas is preferably nitrogen; the reaction is preferably carried out in an organic solvent, and the organic solvent is preferably acetonitrile.

[0047] In the preparation method provided by the present invention, in step c), the reaction temperature is preferably 50-80° C., specifically 60° C.; the reaction time is preferably 12-48 h, specifically 24 h.

[0048] In the preparation method provided by the present invention, in step c), after the reaction is completed, the product is post-treated, and the post-treatment process preferably includes: performing reduced pressure distillation, washing and drying in sequence.

[0049] The present invention also provides a polymer coating, wherein raw materials for preparing the polymer coating include a polymer precursor and a free radical initiator, and the polymer precursor is the polymer precursor described in the above technical solution or a polymer precursor prepared by the preparation method described in the above technical solution.

[0050] In the polymer coating provided by the present invention, the free radical initiator is preferably one or more of a peroxide initiator, an azo compound initiator and a redox initiator, more preferably dibenzoyl peroxide; the mass ratio of the polymer precursor to the free radical initiator is preferably 7.5:(0.02-0.1), specifically 7.5:0.02, 7.5:0.03, 7.5:0.04, 7.5:0.05, 7.5:0.06, 7.5:0.07, 7.5:0.08, 7.5:0.09 or 7.5:0.1.

[0051] In the polymer coating provided by the present invention, the preparation raw materials preferably also include a binder, and the binder is preferably one or more of an acrylic binder, polyvinyl alcohol and sodium carboxymethyl cellulose; the mass ratio of the polymer precursor to the binder is preferably 7.5:(3-7), specifically 7.5:3, 7.5:3.2, 7.5:3.5, 7.5:3.7, 7.5:4, 7.5:4.2, 7.5:4.5, 7.5:4.7, 7.5:5, 7.5:5.2, 7.5:5.5, 7.5:5.7, 7.5:6, 7.5:6.2, 7.5:6.5, 7.5:6.7 or 7.5:7.

[0052] In the polymer coating provided by the present invention, the preparation raw materials preferably also include a conductive agent, and the conductive agent is preferably one or more of acetylene black, natural graphite and artificial graphite; the mass ratio of the polymer precursor to the conductive agent is preferably 7.5:(6-10), specifically 7.5:6, 7.5:6.2, 7.5:6.5, 7.5:6.7, 7.5:7, 7.5:7.2, 7.5:7.5, 7.5:7.7, 7.5:8, 7.5:8.2, 7.5:8.5, 7.5:8.7, 7.5:9, 7.5:9.2, 7.5:9.5, 7.5:9.7 or 7.5:10.

[0053] The present invention also provides a method for preparing the polymer coating described in the above technical solution, comprising the following steps:

[0054] The raw materials for preparing the polymer coating are mixed with water, coated, and baked to obtain the polymer coating.

[0055] In the preparation method provided by the present invention, the solid content of the slurry after the preparation raw materials are mixed with water is preferably 5-20wt%, specifically 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%.

[0056] In the preparation method provided by the present invention, the coating thickness is preferably 1.5 to 3 μm, specifically 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm or 3 μm.

[0057] In the preparation method provided by the present invention, the baking temperature is preferably 80-100°C, specifically 80°C, 85°C, 90°C, 95°C or 100°C; the baking time is preferably 30-60s, specifically 30s, 35s, 40s, 45s, 50s, 55s or 60s.

[0058] The present invention also provides a negative electrode current collector, comprising a negative electrode current collector substrate and a coating coated on the surface of the negative electrode current collector substrate, wherein the coating is the polymer coating described in the above technical solution or the polymer coating prepared by the preparation method described in the above technical solution.

[0059] In the negative electrode current collector provided by the present invention, the material of the negative electrode current collector substrate is preferably copper; and the coating is preferably coated on both the front and back surfaces of the negative electrode current collector substrate.

[0060] The present invention also provides a method for preparing the negative electrode current collector described in the above technical solution, comprising the following steps:

[0061] The raw materials for preparing the polymer coating are mixed with water, coated on the surface of the negative electrode current collector substrate, and baked to obtain the polymer coating. The solid content of the slurry after the raw materials and water are mixed, the coating thickness and the baking conditions can be referred to above and will not be repeated here.

[0062] The present invention also provides a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the current collector of the negative electrode is the negative electrode current collector described in the above technical solution.

[0063] In the lithium ion battery provided by the present invention, the positive electrode includes a positive electrode current collector and a positive electrode coating coated on the surface of the positive electrode current collector; the positive electrode current collector includes but is not limited to aluminum foil; the components of the positive electrode coating include positive electrode active material, conductive agent and binder. In the present invention, the positive electrode active material is preferably lithium cobalt oxide, lithium manganate, ternary nickel cobalt manganese lithium, nickel manganate, lithium iron phosphate or lithium manganese iron phosphate, more preferably ternary nickel cobalt manganese lithium (Ni: Co: Mn = 9: 0.5: 0.5); the conductive agent is preferably conductive carbon black (SuperP) and / or carbon nanotubes (CNT), and the molar ratio of the conductive carbon black to the carbon nanotube is preferably 0.7: (0.5 ~ 1), more preferably 0.7: 0.8; the binder is preferably polyvinylidene fluoride (PVDF); the mass ratio of the positive electrode active material, conductive agent and binder is preferably 97: (0.5 ~ 3): (0.5 ~ 3), more preferably 97: 1.5: 1.5.

[0064] In the lithium-ion battery provided by the present invention, the negative electrode includes a negative electrode current collector and a negative electrode coating coated on the surface of the negative electrode current collector; the negative electrode current collector is the negative electrode current collector described in the above technical solution; the components of the negative electrode coating include negative electrode active material, conductive agent, thickener and binder. In the present invention, the negative electrode active material is preferably artificial graphite, natural graphite, lithium titanate, metallic lithium, silicon-carbon composite material or silicon oxide, more preferably silicon oxide; the conductive agent is preferably conductive carbon black (SuperP); the thickener is preferably sodium carboxymethyl cellulose; the binder is preferably polyacrylic acid; the mass ratio of the negative electrode active material, conductive agent, thickener and binder is preferably 95:(0.5-1.5):(1-2):(2-4), more preferably 95:1:1.5:2.5.

[0065] In the lithium ion battery provided by the present invention, the diaphragm is preferably a polypropylene diaphragm, a polyethylene diaphragm or a polyethylene diaphragm coated with aluminum oxide on one side, more preferably a polyethylene diaphragm coated with aluminum oxide on one side.

[0066] In the lithium ion battery provided by the present invention, the components of the electrolyte preferably include lithium salt, non-aqueous organic solvent and electrolyte additive.

[0067] In the lithium-ion battery provided by the present invention, the lithium salt in the electrolyte is preferably one or more of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and lithium bis(fluorosulfonyl)imide (LiFSI), more preferably lithium hexafluorophosphate.

[0068] In the lithium ion battery provided by the present invention, the non-aqueous organic solvent in the electrolyte is preferably an organic ester solvent and / or an ether solvent. Among them, the organic ester solvent is preferably at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethyl formate, ethyl acetate, propyl acetate, propyl propionate, fluoroethylene carbonate and methyl trifluoroethyl carbonate; the ether solvent is preferably at least one of dimethyl ether, diethyl ether, methyl ethyl ether, ethylene glycol dimethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether. More preferably, ethylene carbonate, propylene carbonate, dimethyl carbonate and ethyl methyl carbonate are selected, and the volume ratio of ethylene carbonate, propylene carbonate, dimethyl carbonate and ethyl methyl carbonate is preferably 5:(8-12):(35-45):(40-50), more preferably 5:10:40:45.

[0069] In the lithium ion battery provided by the present invention, the additive in the electrolyte is preferably vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, di(2,2,2-trifluoroethyl) carbonate, vinyl sulfate, vinyl disulfate, propylene sulfate, 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, 2,4-butane sultone, phenyl methanesulfonate, methylene disulfonate, N-phenylbis(trifluoromethanesulfonyl)imide, triallyl phosphate, tris(trimethylsilane) phosphate, trimethyl phosphite , triphenyl phosphite, tetramethylmethylene diphosphate, propargyl phosphate, (2-allylphenoxy)trimethylsilane, tris(trimethylsilyl)borate, 1,3,5-triallyl isocyanurate, isocyanoethyl methacrylate, hexamethylene diisocyanate, p-phenylene diisocyanate, 2,4-toluene diisocyanate, adiponitrile, succinonitrile, glutaronitrile, 1,3,6-hexanetrinitrile, 1,2-bis(cyanoethoxy)ethane, one or more of lithium difluorophosphate, lithium bisoxalatoborate, lithium difluorooxalatoborate and lithium difluorobisoxalatophosphate. More preferably, one or more of lithium difluorophosphate, 1,3-propane sultone and tris(trimethylsilane) phosphate is selected, and the mass ratio of lithium difluorophosphate, 1,3-propane sultone and tris(trimethylsilane) phosphate is preferably 1:(2-6):(0.5-2), specifically 1:4:1.

[0070] In the lithium ion battery provided by the present invention, the lithium salt preferably accounts for 11-16% of the weight of the electrolyte, and more preferably 12.5%; the non-aqueous organic solvent preferably accounts for 72-85% of the weight of the electrolyte, and more preferably 84.5%; the electrolyte additive preferably accounts for 2-5% of the weight of the electrolyte, and more preferably 3%.

[0071] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects:

[0072] (1) The polymer coating developed by the present invention is used as a surface modification coating for the negative electrode current collector. Since the polymer structure contains anion-cation pairs, in which bromide anions are easily combined with lithium ions, the SEI film on the negative electrode surface can be enriched with LiBr components, thereby providing a lower lithium ion diffusion energy barrier at the interface, thereby improving the stability of interfacial lithium ion transmission.

[0073] (2) The negative electrode current collector developed by the present invention has cationic groups anchored in the surface coating polymer structure, which can attract more anions in the electrolyte to the negative electrode surface to participate in the negative electrode film formation through charge attraction, so that the SEI film contains more inorganic LiF components. The high Young's modulus of LiF greatly improves the mechanical strength of the SEI film, making the SEI film on the surface of the silicon-oxygen negative electrode with a large volume expansion coefficient not easy to rupture during the charge and discharge process, avoiding the continuous proliferation of the SEI film caused by the secondary exposure of the active material, thereby alleviating the gas production and thickening of the battery and the increase of the internal resistance, thereby improving the electrochemical performance of the lithium-ion battery.

[0074] For the purpose of greater clarity, the present invention is described in detail with reference to the following examples and comparative examples.

[0075] Example 1

[0076] The preparation of compound (I) is carried out in the following specific steps:

[0077] (1) Preparation of intermediate product 1, the chemical reaction formula is as follows:

[0078]

[0079] The preparation process is as follows: under a nitrogen atmosphere, add butenedial (0.34 g, 4.00 mmol), 100 mL of anhydrous ethanol and p-benzoquinone (0.86 g, 8.00 mmol) to a clean and dry 150 mL three-necked flask equipped with a magnetic rotor and a reflux condenser, then add 4,5-dimethyl-1,2-phenylenediamine (1.09 g, 8.00 mmol), heat the mixture to 80 ° C and reflux for 4 h. After the reaction mixture is cooled to room temperature, continue to stir and react for 4 h. Then, the solvent is removed by distillation under reduced pressure, and the residual product is washed with 100 mL of 1 mol / L hydrochloric acid aqueous solution. Then, 100 mL of chloroform is used to extract the mixed solution three times, the organic phases are combined, dried over anhydrous magnesium sulfate, and the solvent is removed by rotary evaporation to obtain intermediate product 1 with a yield of 79.2%. HRMS (m / z): calcd.for C 22 H 24N4,344.20, found 344.37.

[0080] (2) Preparation of intermediate product 2, the chemical reaction formula is as follows:

[0081]

[0082] The preparation process is as follows: in a nitrogen atmosphere, to a clean and dry 500mL three-necked flask equipped with a magnetic rotor, add intermediate product 1 (10.33g, 30.00mmol), chloromethylethyldimethylsilane (8.08g, 60.00mmol), potassium hydroxide (4.60g, 82.00mmol) and DMSO (300mL) in sequence, start stirring, and stir the mixture at room temperature for 3h. After the reaction, add 300mL of distilled water pre-frozen to 0°C, then use chloroform (3×100mL) to extract the mixed solution, combine the organic phases, distill off the solvent under reduced pressure, use n-hexane as the eluent, and purify it by a short pad of rapid silica gel chromatography to obtain intermediate compound 2 with a yield of 78.6%. HRMS (m / z): calcd.for C 32 H 44 N4Si2,540.31,found 540.43.

[0083] (3) Preparation of compound (I), the chemical reaction formula is as follows:

[0084]

[0085] The preparation process is as follows: in a nitrogen atmosphere, add intermediate compound 2 (27.02 g, 50.00 mmol) and 200 mL of anhydrous acetonitrile to a clean and dry 500 mL three-necked flask equipped with a magnetic rotor, start stirring, and then slowly add 100 mL of anhydrous acetonitrile solution containing 3-bromopropylene (12.60 g, 105.00 mmol) through a constant pressure dropping funnel. After the addition is complete, the reaction temperature of the system is raised to 60°C, and the stirring reaction is continued for 24 hours. After the reaction is completed, acetonitrile is removed by vacuum distillation. Wash three times with ethyl acetate (3×20 mL), and finally vacuum dry to obtain compound (I), with a yield of 97.5%. EIMS (m / z): calcd.for C 38 H 54 N4Si2 2+ ,311.19,found 311.31.

[0086] The composite modified copper current collector 1 sample was prepared in the following specific steps:

[0087] The polymer precursor compound (I) is mixed with a free radical initiator dibenzoyl peroxide (BPO), a binder sodium carboxymethyl cellulose (CMC), and a conductive agent acetylene black in a mass ratio of 7.5:0.05:5:8, and then deionized water is added at a solid content of 10%, and the slurry is obtained after being evenly dispersed by a double planetary mixer. The slurry is coated on both sides of a 6μm copper foil using a gravure coating, with a single-side coating thickness of 1.5μm, and baked at 100°C for 30s to obtain a composite modified copper current collector, and then the prepared composite modified copper current collector is stored in a drying room with a dew point of -35°C.

[0088] Prepare the standard electrolyte sample. The specific steps are as follows:

[0089] In an argon glove box with a water and oxygen content of ≤0.1ppm, ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are uniformly mixed in a volume ratio of 5:10:40:45 to obtain an organic solvent, and then lithium hexafluorophosphate (LiPF6) is slowly added to the organic solvent, and the temperature of the mixed solution is kept <38°C during the process. Subsequently, lithium difluorophosphate (LiPO2F2), 1,3-propane sultone (PS), and tris(trimethylsilyl) phosphate (TMSP) are added, and the standard electrolyte is obtained after stirring evenly, wherein the usage amounts of LiPF6, organic solvent, LiPO2F2, PS, and TMSP are 12.5%, 84.5%, 0.5%, 2%, and 0.5% of the total mass of the electrolyte, respectively.

[0090] Prepare the experimental battery 1 sample, the specific steps are as follows:

[0091] Preparation of positive electrode sheet: The positive electrode material 9 series nickel cobalt manganese oxide (Ni 0.9 Co 0.05 Mn 0.05 Li), conductive carbon black (SuperP), carbon nanotubes (CNT, 5% by mass NMP solution) and binder polyvinylidene fluoride (PVDF, 5% by mass NMP solution) are weighed and mixed in a mass ratio of 97:0.7:0.8:1.5 (excluding the solvent), and an appropriate amount of NMP is added after mixing to control the theoretical solid content to 65%. A planetary homogenizer is used to homogenize the positive electrode slurry, and the positive electrode slurry is evenly coated on an aluminum foil with a thickness of 13 μm. After drying, rolling and cutting, a 50 mm × 70 mm positive electrode sheet is obtained.

[0092] Preparation of diaphragm: A polyethylene diaphragm coated with aluminum oxide on one side was used as the isolation membrane and was placed in a dry room with a dew point of -35°C for 72 hours before use.

[0093] Preparation of negative electrode sheet: The negative electrode material silicon dioxide (gram capacity 650mAh g-1 ), conductive agent SuperP, thickener sodium carboxymethyl cellulose (CMC, deionized water solution with a solid content of 1.5%), binder polyacrylic acid (PAA, deionized water solution with a solid content of 6%), mixed at a mass ratio of 95:1:1.5:2.5 (excluding solvent), added deionized water after mixing, controlled theoretical solid content of 55%, homogenized by a planetary homogenizer to obtain negative electrode slurry, and evenly coated the negative electrode slurry on the composite modified copper foil prepared above, and obtained 52mm×72mm negative electrode sheet after drying, rolling and cutting. The N / P ratio of positive and negative electrodes is 1.1.

[0094] Preparation of battery: The battery was made in a dry room with an ambient dew point of ≤-35°C, the separator was folded in a Z shape, the positive electrode sheet and the negative electrode sheet were placed on each side, there were 12 layers of positive electrode sheets and 13 layers of negative electrode sheets, the positive electrode, separator and negative electrode were aligned and stacked in order, an alumina-surface separator was coated on the positive electrode to obtain an electrode group, and then the electrode group was fixed with polyimide tape and then the ear was welded, and then placed in an aluminum-plastic film, and then vacuum-baked at 90°C for 12h, and after cooling, the above-prepared standard electrolyte was injected at an injection coefficient of 4.0g / Ah, and finally after vacuum packaging, high-temperature infiltration, formation, aging, secondary sealing and capacity division, an experimental battery 1 with a capacity of about 2.5Ah was obtained.

[0095] Example 2

[0096] The specific steps for preparing compound (II) are as follows:

[0097] (1) Preparation of intermediate product 3, the chemical reaction formula is as follows:

[0098]

[0099] The preparation process is as follows: under a nitrogen atmosphere, to a clean and dry 150mL three-necked flask equipped with a magnetic rotor and a reflux condenser, add butenedial (0.34g, 4.00mmol), 100mL of anhydrous ethanol and p-benzoquinone (0.86g, 8.00mmol), then add 4,5-diamino-o-dibenzonitrile (1.26g, 8.00mmol), and heat the mixture to 80°C and reflux for 4h. After the reaction mixture is cooled to room temperature, the stirring reaction is continued for 4h. The solvent is then removed by distillation under reduced pressure, and the residual product is washed with 100mL of a 1mol / L aqueous hydrochloric acid solution. The mixed solution is then extracted three times with 100mL of chloroform, the organic phases are combined, dried over anhydrous magnesium sulfate, and the solvent is removed by rotary evaporation to obtain intermediate product 3 with a yield of 76.4%. HRMS (m / z): calcd.forC 22 H 12 N8,388.12, found 388.25.

[0100] (2) Preparation of intermediate product 4, the chemical reaction formula is as follows:

[0101]

[0102] The preparation process is as follows: in a nitrogen atmosphere, to a clean and dry 500mL three-necked flask equipped with a magnetic rotor, add the intermediate product 3 (11.64g, 30.00mmol), chloromethylethyldimethylsilane (8.08g, 60.00mmol), potassium hydroxide (4.60g, 82.00mmol) and DMSO (300mL) in sequence, start stirring, and stir the mixture at room temperature for 3h. After the reaction, add 300mL of distilled water pre-frozen to 0°C, then use chloroform (3×100mL) to extract the mixed solution, combine the organic phases, distill off the solvent under reduced pressure, use n-hexane as the eluent, and purify it by a short pad of rapid silica gel chromatography to obtain the intermediate compound 4 with a yield of 77.8%. HRMS (m / z): calcd.for C 32 H 32 N8Si2,584.23,found 584.39.

[0103] (3) Preparation of compound (II), the chemical reaction formula is as follows:

[0104]

[0105] The preparation process is as follows: in a nitrogen atmosphere, add intermediate compound 4 (29.21 g, 50.00 mmol) and 200 mL of anhydrous acetonitrile to a clean and dry 500 mL three-necked flask equipped with a magnetic rotor, start stirring, and then slowly add 100 mL of anhydrous acetonitrile solution containing 3-bromopropylene (12.60 g, 105.00 mmol) through a constant pressure dropping funnel. After the addition is complete, the reaction temperature of the system is raised to 60°C, and the stirring reaction is continued for 24 hours. After the reaction is completed, acetonitrile is removed by vacuum distillation. Wash three times with ethyl acetate (3×20 mL), and finally vacuum dry to obtain compound (II) with a yield of 97.0%. EIMS (m / z): calcd.for C 38 H 42 N8Si2 2+ ,333.15,found 333.23.

[0106] The composite modified copper current collector 2 sample was prepared according to the method of Example 1, except that the polymer precursor compound (II) was used in the composite modified copper current collector 2 sample.

[0107] The standard electrolyte was prepared according to the method of Example 1.

[0108] An experimental battery 2 was prepared according to the method of Example 1, except that the current collector used for the negative electrode was the composite modified copper current collector 2 prepared above.

[0109] Example 3

[0110] (1) Preparation of intermediate product 5, the chemical reaction formula is as follows:

[0111]

[0112] The preparation process is as follows: under nitrogen atmosphere, add butenedial (0.34 g, 4.00 mmol), 100 mL of anhydrous ethanol and p-benzoquinone (0.86 g, 8.00 mmol) to a clean and dry 150 mL three-necked flask equipped with a magnetic rotor and a reflux condenser, then add 4,5-diamino-2-trifluoromethylbenzonitrile (1.61 g, 8.00 mmol), heat the mixture to 80 ° C and reflux for 4 h. After the reaction mixture is cooled to room temperature, continue to stir and react for 4 h. Then, the solvent is removed by distillation under reduced pressure, and the residual product is washed with 100 mL of 1 mol / L hydrochloric acid aqueous solution. Then, 100 mL of chloroform is used to extract the mixed solution three times, the organic phases are combined, dried over anhydrous magnesium sulfate, and the solvent is removed by rotary evaporation to obtain intermediate product 5 with a yield of 75.3%. HRMS (m / z): calcd.for C 22 H 12 F6N6,474.10,found474.20.

[0113] (2) Preparation of intermediate product 6, the chemical reaction formula is as follows:

[0114]

[0115] The preparation process is as follows: in a nitrogen atmosphere, to a clean and dry 500mL three-necked flask equipped with a magnetic rotor, add intermediate product 5 (14.10g, 30.00mmol), chloromethylethyldimethylsilane (8.08g, 60.00mmol), potassium hydroxide (4.60g, 82.00mmol) and DMSO (300mL) in sequence, start stirring, and stir the mixture at room temperature for 3h. After the reaction is completed, 300mL of distilled water pre-frozen to 0°C is added, and then the mixed solution is extracted with chloroform (3×100mL), the organic phases are combined, the solvent is distilled off under reduced pressure, and n-hexane is used as the eluent. After purification by a short pad of rapid silica gel chromatography, intermediate compound 6 is obtained with a yield of 78.4%. HRMS (m / z): calcd.forC 32 H 32 F6N6Si2,670.21, found 670.33.

[0116] (3) Preparation of compound (III), the chemical reaction formula is as follows:

[0117]

[0118] The preparation process is as follows: in a nitrogen atmosphere, add intermediate compound 6 (33.51 g, 50.00 mmol) and 200 mL of anhydrous acetonitrile to a clean and dry 500 mL three-necked flask equipped with a magnetic rotor, start stirring, and then slowly add 100 mL of anhydrous acetonitrile solution containing 3-bromopropylene (12.60 g, 105.00 mmol) through a constant pressure dropping funnel. After the addition is complete, the reaction temperature of the system is raised to 60°C, and the stirring reaction is continued for 24 hours. After the reaction is completed, acetonitrile is removed by vacuum distillation. Wash three times with ethyl acetate (3×20 mL), and finally vacuum dry to obtain compound (III) with a yield of 96.3%. EIMS (m / z): calcd.for C 38 H 42 F6N6Si2 2+ ,376.15,found 376.19.

[0119] The composite modified copper current collector 3 sample was prepared according to the method of Example 1, except that the polymer precursor compound (III) was used in the composite modified copper current collector 3 sample.

[0120] The standard electrolyte was prepared according to the method of Example 1.

[0121] An experimental battery 3 was prepared according to the method of Example 1, except that the current collector used for the negative electrode was the composite modified copper current collector 3 prepared above.

[0122] Example 4

[0123] (1) Preparation of intermediate product 7, the chemical reaction formula is as follows:

[0124]

[0125] The preparation process is as follows: under a nitrogen atmosphere, add butenedial (0.34 g, 4.00 mmol), 100 mL of anhydrous ethanol and p-benzoquinone (0.86 g, 8.00 mmol) to a clean and dry 150 mL three-necked flask equipped with a magnetic rotor and a reflux condenser, then add 4-ethynylbenzene-1,2-diamine (1.06 g, 8.00 mmol), heat the mixture to 80 ° C and reflux for 4 h. After the reaction mixture is cooled to room temperature, continue to stir and react for 4 h. Then, the solvent is removed by distillation under reduced pressure, and the residual product is washed with 100 mL of 1 mol / L hydrochloric acid aqueous solution. Then, 100 mL of chloroform is used to extract the mixed solution three times, the organic phases are combined, dried over anhydrous magnesium sulfate, and the solvent is removed by rotary evaporation to obtain intermediate product 7 with a yield of 78.4%. HRMS (m / z): calcd.forC 22 H 16 N4,336.14, found 336.28.

[0126] (2) Preparation of intermediate product 8, the chemical reaction formula is as follows:

[0127]

[0128] The preparation process is as follows: in a nitrogen atmosphere, to a clean and dry 500mL three-necked flask equipped with a magnetic rotor, add intermediate product 7 (10.08g, 30.00mmol), chloromethylethyldimethylsilane (8.08g, 60.00mmol), potassium hydroxide (4.60g, 82.00mmol) and DMSO (300mL) in sequence, start stirring, and stir the mixture at room temperature for 3h. After the reaction is completed, add 300mL of distilled water pre-frozen to 0°C, then use chloroform (3×100mL) to extract the mixed solution, combine the organic phases, distill off the solvent under reduced pressure, use n-hexane as the eluent, and purify it by a short pad of rapid silica gel chromatography to obtain intermediate compound 8 with a yield of 78.9%. HRMS (m / z): calcd.for C 32 H 36 N4Si2,532.25,found 532.42.

[0129] (3) Preparation of compound (IV), the chemical reaction formula is as follows:

[0130]

[0131] The preparation process is as follows: in a nitrogen atmosphere, add intermediate compound 8 (26.61 g, 50.00 mmol) and 200 mL of anhydrous acetonitrile to a clean and dry 500 mL three-necked flask equipped with a magnetic rotor, start stirring, and then slowly add 100 mL of anhydrous acetonitrile solution containing 3-bromopropylene (12.60 g, 105.00 mmol) through a constant pressure dropping funnel. After the addition is complete, the reaction temperature of the system is raised to 60°C, and the stirring reaction is continued for 24 hours. After the reaction is completed, acetonitrile is removed by vacuum distillation. Wash three times with ethyl acetate (3×20 mL), and finally vacuum dry to obtain compound (IV) with a yield of 96.9%. EIMS (m / z): calcd.for C 38 H 46 N4Si2 2+ ,307.16,found 307.21.

[0132] The composite modified copper current collector 4 sample was prepared according to the method of Example 1, except that the polymer precursor compound (IV) was used in the composite modified copper current collector 4 sample.

[0133] The standard electrolyte was prepared according to the method of Example 1.

[0134] An experimental battery 4 was prepared according to the method of Example 1, except that the current collector used for the negative electrode was the composite modified copper current collector 4 prepared above.

[0135] Example 5

[0136] (1) Preparation of intermediate product 9, the chemical reaction formula is as follows:

[0137]

[0138] The preparation process is as follows: under a nitrogen atmosphere, to a clean and dry 150mL three-necked flask equipped with a magnetic rotor and a reflux condenser, add butenedial (0.34g, 4.00mmol), 100mL of anhydrous ethanol and p-benzoquinone (0.86g, 8.00mmol), then add 4,5-difluorobenzene-1,2-diamine (1.15g, 8.00mmol), and heat the mixture to 80°C and reflux for 4h. After the reaction mixture is cooled to room temperature, the stirring reaction is continued for 4h. The solvent is then removed by distillation under reduced pressure, and the residual product is washed with 100mL of a 1mol / L aqueous hydrochloric acid solution. The mixed solution is then extracted three times with 100mL of chloroform, the organic phases are combined, dried over anhydrous magnesium sulfate, and the solvent is removed by rotary evaporation to obtain the intermediate product 9 with a yield of 75.1%. HRMS (m / z): calcd.forC 18 H 12 F4N4,360.10,found 360.23.

[0139] (2) Preparation of intermediate product 10, the chemical reaction formula is as follows:

[0140]

[0141] The preparation process is as follows: in a nitrogen atmosphere, to a clean and dry 500mL three-necked flask equipped with a magnetic rotor, add the intermediate product 7 (10.80g, 30.00mmol), chloromethylethyldimethylsilane (8.08g, 60.00mmol), potassium hydroxide (4.60g, 82.00mmol) and DMSO (300mL) in sequence, start stirring, and stir the mixture at room temperature for 3h. After the reaction is completed, add 300mL of distilled water pre-frozen to 0°C, then use chloroform (3×100mL) to extract the mixed solution, combine the organic phases, distill off the solvent under reduced pressure, use n-hexane as the eluent, and purify it by a short pad of rapid silica gel chromatography to obtain the intermediate compound 10 with a yield of 76.7%. HRMS (m / z): calcd.for C 28 H 32 F4N4Si2,556.21, found 556.37.

[0142] (3) Compound (V) is prepared, and the chemical reaction formula is as follows:

[0143]

[0144] The preparation process is as follows: in a nitrogen atmosphere, add intermediate compound 10 (27.81 g, 50.00 mmol) and 200 mL of anhydrous acetonitrile to a clean and dry 500 mL three-necked flask equipped with a magnetic rotor, start stirring, and then slowly add 100 mL of anhydrous acetonitrile solution containing 3-bromopropylene (12.60 g, 105.00 mmol) through a constant pressure dropping funnel. After the addition is complete, the reaction temperature of the system is raised to 60°C, and the stirring reaction is continued for 24 hours. After the reaction is completed, acetonitrile is removed by vacuum distillation. Wash three times with ethyl acetate (3×20 mL), and finally vacuum dry to obtain compound (V), with a yield of 94.9%. EIMS (m / z): calcd.for C 34 H 42 F4N4Si2 2+ ,319.14,found 319.28.

[0145] The composite modified copper current collector 5 sample was prepared according to the method of Example 1, except that the polymer precursor compound (V) was used in the composite modified copper current collector 5 sample.

[0146] The standard electrolyte was prepared according to the method of Example 1.

[0147] An experimental battery 5 was prepared according to the method of Example 1, except that the current collector used for the negative electrode was the composite modified copper current collector 5 prepared above.

[0148] Example 6

[0149] (1) Preparation of intermediate product 9, the chemical reaction formula is as follows:

[0150]

[0151] The preparation process is as follows: under a nitrogen atmosphere, to a clean and dry 150mL three-necked flask equipped with a magnetic rotor and a reflux condenser, add butenedial (0.34g, 4.00mmol), 100mL of anhydrous ethanol and p-benzoquinone (0.86g, 8.00mmol), then add 4,5-bis(trifluoromethyl)benzene-1,2-diamine (1.95g, 8.00mmol), and heat the mixture to 80°C and reflux for 4h. After the reaction mixture is cooled to room temperature, the stirring reaction is continued for 4h. The solvent is then removed by distillation under reduced pressure, and the residual product is washed with 100mL of a 1mol / L aqueous hydrochloric acid solution. The mixed solution is then extracted three times with 100mL of chloroform, the organic phases are combined, dried over anhydrous magnesium sulfate, and the solvent is removed by rotary evaporation to obtain the intermediate product 11 with a yield of 72.8%. HRMS (m / z): calcd.for C 22 H 12 F 12 N4,560.09, found 560.26.

[0152] (2) Preparation of intermediate product 11, the chemical reaction formula is as follows:

[0153]

[0154] The preparation process is as follows: in a nitrogen atmosphere, to a clean and dry 500mL three-necked flask equipped with a magnetic rotor, add the intermediate product 11 (16.80g, 30.00mmol), chloromethylethyldimethylsilane (8.08g, 60.00mmol), potassium hydroxide (4.60g, 82.00mmol) and DMSO (300mL) in sequence, start stirring, and stir the mixture at room temperature for 3h. After the reaction, add 300mL of distilled water pre-frozen to 0°C, then use chloroform (3×100mL) to extract the mixed solution, combine the organic phases, distill off the solvent under reduced pressure, use n-hexane as the eluent, and purify it by a short pad of rapid silica gel chromatography to obtain the intermediate compound 12 with a yield of 74.3%. HRMS (m / z): calcd.for C 32 H 32 F 12N4Si2,756.20,found 756.39.

[0155] (3) Preparation of compound (VI), the chemical reaction formula is as follows:

[0156]

[0157] The preparation process is as follows: in a nitrogen atmosphere, add intermediate compound 12 (37.81 g, 50.00 mmol) and 200 mL of anhydrous acetonitrile to a clean and dry 500 mL three-necked flask equipped with a magnetic rotor, start stirring, and then slowly add 100 mL of anhydrous acetonitrile solution containing 3-bromopropylene (12.60 g, 105.00 mmol) through a constant pressure dropping funnel. After the addition is complete, the reaction temperature of the system is raised to 60°C, and the stirring reaction is continued for 24 hours. After the reaction is completed, acetonitrile is removed by vacuum distillation. Wash three times with ethyl acetate (3×20 mL), and finally vacuum dry to obtain compound (VI) with a yield of 92.5%. EIMS (m / z): calcd.for C 38 H 42 F 12 N4Si2 2+ ,419.14,found419.24.

[0158] The composite modified copper current collector 6 sample was prepared according to the method of Example 1, except that the polymer precursor compound (VI) was used in the composite modified copper current collector 6 sample.

[0159] The standard electrolyte was prepared according to the method of Example 1.

[0160] An experimental battery 6 was prepared according to the method of Example 1, except that the current collector used for the negative electrode was the composite modified copper current collector 6 prepared above.

[0161] Example 7

[0162] A composite modified copper current collector 7 sample was prepared according to the method of Example 1, except that a polymer precursor compound (V) was used in the composite modified copper current collector 7 sample, and the mass ratio of compound (V) to free radical initiator BPO, binder CMC, and conductive agent acetylene black was 7.5:0.02:3:6, the coating slurry solid content was 5wt%, and the single-sided coating thickness was 2.0μm.

[0163] The standard electrolyte was prepared according to the method of Example 1.

[0164] An experimental battery 7 was prepared according to the method of Example 1, except that the current collector used for the negative electrode was the composite modified copper current collector 7 prepared above.

[0165] Example 8

[0166] A composite modified copper current collector 8 sample was prepared according to the method of Example 1, except that a polymer precursor compound (V) was used in the composite modified copper current collector 8 sample, and the mass ratio of compound (V) to free radical initiator BPO, binder CMC, and conductive agent acetylene black was 7.5:0.1:7:10, the coating slurry solid content was 15wt%, and the single-sided coating thickness was 2.5μm.

[0167] The standard electrolyte was prepared according to the method of Example 1.

[0168] An experimental battery 8 was prepared according to the method of Example 1, except that the current collector used for the negative electrode was the composite modified copper current collector 8 prepared above.

[0169] Example 9

[0170] A composite modified copper current collector 9 sample was prepared according to the method of Example 1, except that a polymer precursor compound (V) was used in the composite modified copper current collector 9 sample, the coating slurry solid content was 20wt%, the single-sided coating thickness was 3μm, the baking temperature was 80°C, and the baking time was 60s.

[0171] The standard electrolyte was prepared according to the method of Example 1.

[0172] An experimental battery 9 was prepared according to the method of Example 1, except that the current collector used for the negative electrode was the composite modified copper current collector 9 prepared above.

[0173] Comparative Example 1

[0174] The experimental battery 10 was prepared according to the method of Example 1, except that the negative electrode current collector of the experimental battery 10 sample used a commercially available 9 μm carbon-coated copper foil.

[0175] Comparative Example 2

[0176] The experimental battery 11 was prepared according to the method of Example 1, except that the negative electrode current collector of the experimental battery 11 sample used a commercially available 9 μm smooth copper foil.

[0177] Performance Testing

[0178] The lithium ion batteries prepared in Examples 1 to 9 and Comparative Examples 1 to 2 were subjected to high temperature long cycle performance tests and rate cycle performance tests, respectively, and the test conditions were as follows:

[0179] Battery high temperature long cycle test

[0180] The prepared lithium-ion battery was first measured for the initial battery internal resistance R0 using an internal resistance tester, and then placed in an explosion-proof oven at an ambient temperature of 45°C, and charged at a constant current and constant voltage with a current of 1C and a voltage of 4.2V until the cut-off current was 0.05C, and then discharged at a constant current of 1C to a voltage of 3V, and cycled for 1000 weeks, and the capacity retention rate was recorded. The capacity retention rate of the nth cycle (%) = (the discharge capacity of the nth cycle / the discharge capacity of the first cycle) × 100%. After the test was completed, the battery internal resistance R1 was measured after cooling to room temperature, and the internal resistance (ACR) growth rate (%) = (R1-R0) × 100% / V0. Four batteries were tested in each group and the average value was taken.

[0181] Rate performance test

[0182] Before the test, the battery was subjected to an initial charge and discharge operation at room temperature at 0.2C, and then continued to be charged at room temperature at a current of 0.2C and a voltage of 4.2V, with constant current and constant voltage until the cut-off current was 0.05C, and then discharged at a constant current of 5C to 3V, 5C discharge capacity retention rate (%) = (5C discharge capacity / 0.2C discharge capacity) × 100%.

[0183] Before the test, the battery was charged and discharged at room temperature at 0.2C initially, then continued to be charged at room temperature at a constant current of 5C to a cut-off voltage of 4.2V, and then discharged at a constant current of 0.2C to 3V. 5C charging capacity retention rate (%) = (5C charging capacity / 0.2C charging capacity) × 100%. Four batteries were tested in each group and the average value was taken.

[0184] Table 1. Negative current collectors and corresponding battery performance of various embodiments and comparative examples

[0185]

[0186]

[0187] High nickel lithium ion batteries were prepared using the electrolytes prepared in Examples 1 to 9 and Comparative Examples 1 to 2. The battery performance test results are shown in Table 1. It can be seen that the negative electrode current collector prepared by the modification method of the negative electrode current collector provided by the present invention is applied to high nickel lithium ion batteries, and the expected excellent high temperature performance and rate performance are achieved. Compared with the commercially available negative electrode copper current collector that is not modified or coated with conductive carbon black, the battery performance has a significant improvement effect, and the battery internal resistance remains stable or only increases slightly during the cycle, which can be attributed to the high stability of the negative electrode interface SEI during high temperature cycles. Thanks to the use of the modified negative electrode current collector provided by the present invention, the SEI film contains more inorganic LiF components, and thus the SEI film has higher mechanical strength, so that the SEI film on the surface of the silicon oxygen negative electrode with a large volume expansion coefficient is not easy to break during the charge and discharge process, and the SEI film caused by the secondary exposure of the active material is avoided. Continued hyperplasia of the SEI film is avoided, thereby alleviating the thickening of the battery gas production and the increase of the internal resistance, thereby improving the electrochemical performance of the lithium ion battery.

[0188] At the same time, by comparing Examples 1 to 6 and Examples 7 to 9, it can be seen that the modification method of the negative electrode current collector is that the solid content of the coating slurry should not be too high, and the coating thickness should not be too thick. Too high a solid content will result in excessive viscosity of the coating slurry during the actual production and preparation process, which will lead to uneven coating. Too thick a coating thickness will not bring more significant performance improvements, and may even have a negative impact. Therefore, the optimal solid content of the coating slurry is 10%, and the optimal coating thickness is 1.5 μm, which can take into account both the production and preparation of the modified negative electrode current collector and the performance effect of its application in lithium-ion batteries.

[0189] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A polymer precursor, characterized in that The chemical structure of the polymer precursor is shown in Formula A: Wherein, X is Br, and R1 and R2 are selected from one or more of a methyl group, a cyano group, an ethynyl group, a hydrogen atom, a fluorine atom and a trifluoromethyl group.

2. The polymer precursor according to claim 1, characterized in that The polymer precursor is at least one of the compounds of formula (I) to formula (VI):

3. A method for preparing a polymer precursor, characterized in that: The following steps are involved: a) subjecting an o-diamino compound of formula a to an addition reaction with butenedial to obtain a diimidazole intermediate of formula b; b) grafting the diimidazole intermediate of formula b with chloromethylethyldimethylsilane to obtain an intermediate of formula c; c) reacting the intermediate of formula c with a halogenated olefin of formula d to obtain a polymer precursor of formula a; Wherein, X is Br, and R1 and R2 are independently selected from one or more of a methyl group, a cyano group, an ethynyl group, a hydrogen atom, a fluorine atom and a trifluoromethyl group.

4. A polymer coating, characterized in that The raw materials for preparing the polymer coating include a polymer precursor and a free radical initiator. The polymer precursor is the polymer precursor described in claim 1 or 2 or the polymer precursor prepared by the preparation method described in claim 3.

5. The polymer coating according to claim 4, characterized in that The free radical initiator is one or more of a peroxide initiator, an azo compound initiator and a redox initiator; the mass ratio of the polymer precursor to the free radical initiator is 7.5:(0.02-0.1).

6. The polymer coating according to claim 4, characterized in that The preparation raw materials also include a binder and a conductive agent; the binder is one or more of an acrylic binder, polyvinyl alcohol and sodium carboxymethyl cellulose; the conductive agent is one or more of acetylene black, natural graphite and artificial graphite; the mass ratio of the polymer precursor, the binder and the conductive agent is 7.5:(3-7):(6-10).

7. A method for preparing a polymer coating according to any one of claims 4 to 6, characterized in that: The following steps are involved: The raw materials for preparing the polymer coating are mixed with water, coated, and baked to obtain the polymer coating.

8. A negative electrode current collector, characterized in that: The negative electrode current collector comprises a negative electrode current collector substrate and a coating coated on the surface of the negative electrode current collector substrate, wherein the coating is the polymer coating according to any one of claims 4 to 6 or the polymer coating prepared by the preparation method according to claim 7.

9. The negative electrode current collector according to claim 8, characterized in that: The negative electrode current collector substrate is made of copper.

10. A lithium ion battery, characterized in that: The negative electrode current collector of the lithium ion battery is the negative electrode current collector according to claim 8 or 9.

Citation Information

Patent Citations

  • Negative electrode, negative active material, method of preparing the negative electrode, and lithium battery including the negative electrode

    CN102593419A

  • Metal lithium battery negative electrode, preparation method thereof and lithium secondary battery

    CN112635766A

  • Preparation method of acrylate-based polymer solid electrolyte and lithium ion battery

    CN115472906A

  • Rechargeable batteries with improved low temperature performance

    US20240243369A1